Atividade prebiótica dos carboidratos extraídos do farelo de arroz desengordurado - Antunes, Laura Luisi (2021)
Rice bran, a by-product of rice processing, represents about 6 – 12% of the grain in natura, with a rich nutrient composition, especially high concentrations of carbohydrates with potential prebiotic effect. The aim of this study was to evaluate the prebiotic activity of carbohydrates (CHO) extracted from defatted rice bran (DRB) by ultrasound-assisted extraction (CRBU) and hydrothermal treatment (CRBH), by evaluating the in vitro digestibility of sugars, its potential for use as a sugar source for the growth of probiotic microorganisms (L. acidophilus LA-05, L. casei-01, L. plantarum BG 112 e L. rhamnosus ATCC 53103), prebiotic activity score and bacterial metabolic activity (pH values, sugar consumption and acid production). The extracts (CRBU and CRBH) were also characterized for their total carbohydrate content, extraction yield, carbohydrate profile and functional groups. The ultrasonic method was more efficient in the extraction of carbohydrates (0.590 ± 0.001 g CHO g-1 extract and 96.72% yield) compared to the hydrothermal treatment (0.507 ± 0.004 g CHO g-1 extract and 83.11% yield). The two extracts were similar regarding the FTIR spectrum and the carbohydrate profile, with the presence of the glucose, stachyose and arabinose in its composition. CRBU and CRBH demonstrated a low degree of hydrolysis under in vitro digestibility conditions, mainly at an initial concentration of 15 g L-1 of sample (4.44 ± 0.48% and 5.72 ± 1.50%, respectively), increasing at a concentration of 30 g L-1 (11.74 ± 0.18% and 17.99 ± 2.44%, respectively). Assays with CRBU and CRBH provided similar counts (p > 0.05) of viable probiotic cells (> 8.0 and 8.8 log CFU mL-1 at the concentration of 15 and 30 g L-1 , respectively) after 48 h of cultivation, as well as positive prebiotic activity scores (0.38 – 0.83 and 0.36 – 0.64, at the concentration of 15 and 30 g L-1 , respectively); it was also verified in the media, a decrease in pH, production of lactic acid, acetic acid and propionic acid, and consumption of glucose, fructose and stachyose over time. These results demonstrate that defatted rice bran carbohydrates can be considered as a potential source of prebiotics.